Propagation of the compaction waves in a cellular block with varying cross-section. (15th June 2016) - Shen, C.J.; Lu, G.; Ruan, D.; Yu, T.X.
Highlights: Experimental studies on the aluminum foam specimen with varying cross-section under impact are carried out. Two deformations modes are identified and corresponding force histories are recorded. Improved analytical models are proposed, incorporating the strain hardening effect of the aluminum foam. The propagation of the plastic waves in the graded foam block under impact is described. Parametrical studies are implemented for the double shock mode. Abstract: Current work aims to broaden our previous work on the compaction waves in a cellular block with varying cross-section under impact. Complement experiments were carried out to obtain the force signals of the foam specimen with varying cross-section in the dynamic crushing. Two impact scenarios were employed. In the first impact scenario, the foam block together with a back mass impinged onto a rigid target; and in the second scenario, a stationary foam block was impinged by a rigid mass. The foam/mass was fired from a gas gun barrel. The impact velocity was measured before the impact happened. The deformation processes were captured by a high speed camera and an aluminum bar was served as the rigid target. Two groups of semi-conductive strain gauges were attached at the surface of the bar to obtain the strain/stress signals. Typical force signals were analyzed together with their deformation processes. Then, an improved analytical model is proposed, incorporating the strain hardening property of the aluminum foam. Comparisons are made between the analytical models and experimental results, showing that the proposed model is able to predict the dynamic forces with sufficient accuracy. Based on the modified analytical model, typical propagations of the compaction wave are described. Correspondingly, parametrical studies are implemented based on the proposed analytical model.